Iron deficiency anemia in infants. Preliminary development results at five years - Antunes, H (2005)
INTRODUCTION: Research, mostly conducted in developing countries, have suggested short and long term developmental delay in children who had iron-deficiency anemia (IDA) in their early life. This study aims to evaluate the development of 5-years old children who were diagnosed IDA at 9 months of age. METHODS: 27 children with IDA diagnosed at 9 months of age and 28 non-anemic controls were followed-up until they were 5 years old. At 9 months of age and at 5 years of age, blood samples were collected for blood count, iron, transferrin and ferritin. Children with hemoglobin < 110 g/l and ferritin < 12 ng/ml were diagnosed with IDA and received iron treatment for IDA correction. C Reactive Protein and antibody to hepatitis A virus were also studied at 5 years of age. At this age, children's motor and cognitive development were accessed using Griffith's test. RESULTS: At 9 months of age, IDA children had [mean (SD)] 102.5 g/ l (5.9) g/l of hemoglobin and 5.6 ng/l (3.1) ng/ml of ferritin. At 5 years of age all children were healthy and without anemia. One child had positive antibody to hepatitis A virus. The results of Griffith's test at five years--anemic/non-anemic at 9 months of age. The mean (sd)-p: general coefficient--100.8 (6.6)/99.5 (7.1)-0.48; locomotor 110.2 (6.9)/109.3 (6.5)-0.62; personal-social--99.1 (11.4)/95.7(11.6)-0.28; hearing-speech--93.8 (9.1)/95.3 (13.7)-0.64; hand-eye--98.2 (13.2)/99.1 (14.3)-0.79; performance--97.5 (17.6)/96.9 (13.6)-0.88; practical reasoning--89.8 (9.1)/86.3(7.1)-0.21. CONCLUSIONS: As only one child had positive antibody to hepatitis A virus, the study population may be considered as belonging to a developed region. These results suggest that, at least in developed regions, infants who receive an early treatment for their mild IDA may not be affected in global development at the age of five.